The fabric of life: Improving the university experience for students who self-identify as having a mental health problem - Wynaden, Dianne (Wiley-Blackwell Publishing Asia, 2012)
The university environment is a diverse community and many students have a diagnosed mental illness or self-identify as experiencing a mental health problem. Many do not seek professional help and this can impact on their ability to complete their university studies. A Higher Education Equity Support Program grant was used to improve the university experience for this group of students. The aims were to increase the knowledge and skills of staff and students about mental illness; to decrease stigma within the university; and identify resources, training and administrative processes that would improve the educational and social out- comes for students. Mental Health First Aid was run for university staff and a designated Mental Health @Curtin website was developed. This facilitated access to information on mental illness and how to find assistance within and outside of the university. An online survey obtained feedback on the problems that this group of students faced. Approximately 2500 students completed the questionnaire and the findings presented here highlight the need for additional training for all staff; the ongoing need to address stigma within the university environment and flexibility regarding course requirements and learning methods. The high rates of students who struggle with mental health problems while completing their tertiary studies makes this a significant issue. The outcome of this research has facilitated further education and training for staff and the appointment of a designated mental health counsellor. Enabling students to complete their educational programs is a major step in the road to mental health and wellbeing in this group.